2017
DOI: 10.1111/2041-210x.12773
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the probability of microhabitat formation on trees using cross‐sectional data

Abstract: Accepted ArticleThis article is protected by copyright. All rights reserved.TreM fluxes will help to design forest biodiversity conservation strategies favouring the development and temporal continuity of TreMs. Tweetable AbstractThe rate of TreM formation per unit diameter growth was modelled as a function of tree diameter at breast height (DBH), and the model was calibrated considering cross-sectional observations TreMs on trees of different sizes. The model predicted realistic TreM formation rates at the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
36
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 38 publications
(104 reference statements)
7
36
1
Order By: Relevance
“…Numerous recent studies in various contexts showed that the number of microhabitats per tree, as well as the occurrence of some types increase with tree diameter [10,13,15] and showed higher levels on dead than living trees [11,12]. Our nationwide study based on a large tree database confirmed these relationships and extend them to a larger range of tree species in various biogeographical conditions than before.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Numerous recent studies in various contexts showed that the number of microhabitats per tree, as well as the occurrence of some types increase with tree diameter [10,13,15] and showed higher levels on dead than living trees [11,12]. Our nationwide study based on a large tree database confirmed these relationships and extend them to a larger range of tree species in various biogeographical conditions than before.…”
Section: Discussionsupporting
confidence: 82%
“…Models allowing for different link functions – probably within a Bayesian framework – remain to be tested to see whether they perform better than the current ones used (see e.g. [10]).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations